A printable hydrogel microarray for drug screening avoids false positives associated with promiscuous aggregating inhibitors - Rabia Mateen (Nature Portfolio, 2018)
False positive results significantly slow down the drug discovery process. Here, the authors developed a gel serving as a screening platform in which enzymes can be stored, stabilized, and protected from most of the compounds that typically cause these misleading results.